Institutional change in higher education: a case study - Bleazard, David Keith (School of Education, 2023)
The dissertation, "Institutional Change in Higher Education: A Case Study" examines efforts to bring about fundamental institutional change at the University of Natal over a period of some 1 0 years, 1988 to 1997. The case study is characterised as being of an embedded single case design. It is an instrumental rather than an intrinsic study. It attempts to extend understanding of the complex social phenomenon of institutional change in higher education, through analytic generalization. The two sub-units of the case study relate to different attempts by the executive of the University of Natal to bring about consensus on the need for fundamental change and the nature of the change: through a more-or-less conventional strategic planning process; and by the adoption- as a strategic initiative- of the notion of becoming a learning organization. The two sub units are examined on the strength of University documents and interviews with past and present University office bearers and staff, within a conceptual framework of organizational theory derived mainly from Mintzberg, McGregor, and Senge. Both the strategic planning approach and the learning organization approach are seen to have failed as means of engineering consensual change and in the latter half of 1997 the University experiences a restructuring crisis as a result of financial pressures. A puzzle around restructuring, viz. why the University should pursue structural change which goes beyond the needs of simple cost-cutting and efficiency, is addressed first in terms of a perceived need for innovation, within the foregoing organizational theoretical framework. The analysis is then extended (effectively recontextualised) within a more pedagogic, social and political theoretical framework which is dependent largely on Bernstein. This analysis sees the changes being pursued at the University of Natal as being consistent with a shift in higher education generally to a market-dominated, competitive discourse in which University lecturers become knowledge entrepreneurs, competing within the institution and between institutions for scarce resources in response to perceived market needs. In this process, the narcissistic and introjected identities of academic departments, in which professionals in bounded disciplines determine priorities themselves, are replaced by projected identities and priorities are determined outside the discipline and the University. This cannot happen overnight. However, plans at the University of Natal to remove their administrative authority from academic departments are seen as a step in this direction.